Robotic Aortic Annular Enlargement With Y-Incision and Rectangular Patch - Ahsan Ehtesham (17316907) (2025)
Surgical enlargement of the aortic annulus enables insertion of a larger prosthetic valve, avoiding patient–prosthesis mismatch (PPM). Although several aortic annular enlargement techniques have been described, the rectangular patch technique with an inverted Y-incision along the left and noncoronary cusps is relatively recent. These procedures are technically challenging via minimally invasive approaches, but robotic assistance makes them possible. The patient had symptomatic severe aortic valve stenosis with evidence of left ventricular dysfunction (ejection fraction = 45%, peak gradient = 47.2 mm Hg, mean gradient = 29.3 mm Hg, and aortic valve area = 0.6 cm2). Preoperative computed tomography measured the aortic annulus at 18 mm (patient body surface area = 1.9). Notably, moderate aortic stenosis was documented 6 months earlier with preserved ejection fraction (55% to 65%), indicating rapid disease progression. Other Information Published in: Innovations: Technology and Techniques in Cardiothoracic and Vascular Surgery License: https://creativecommons.org/licenses/by/4.0/ See article on publisher's website: https://dx.doi.org/10.1177/15569845251375582